Community-Based Participatory Research and Sustainability: The Petersburg Wellness Consortium - Maghboeba Mosavel; Jodi Winship; Valerie Liggins; Tiffany Cox; Mike Roberts; Debra S. Jones (The University of Alabama, 2022)
The principle and practice of sustainability is critical in community-based participatory research. Actively planning for and building community capacity to ensure sustainability is even more critical in research involving underserved populations and underrepresented minorities. The perception of researchers engaging with the community until their research needs have been met, then leaving the community with minimal, if any benefits, has all too often been the reality in these communities. This paper offers a case study of how an independent community consortium was borne from an academic/community research partnership in Petersburg, Virginia. We discuss lessons learned and practice implications as we describe the evolution of, and challenges associated with, cultivating a sustainable independent coalition.